2016
DOI: 10.1007/s00247-016-3712-x
|View full text |Cite
|
Sign up to set email alerts
|

The Daily Readiness Huddle: a process to rapidly identify issues and foster improvement through problem-solving accountability

Abstract: The Daily Readiness Huddle process has given us a framework to rapidly identify issues, bring accountability to problem-solving, and foster improvement. It has also had a positive effect on team-building and coordination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 2 publications
2
24
0
Order By: Relevance
“…There was a general consensus as to what the most important operational features are and a high degree of belief in the venture. This is something that has been identified in other, mostly US, studies (Goldenhar et al 2013;Verschoor et al 2007;Freitag & Carroll 2011;Donnelly et al 2017;Glymph et al 2015;Wagner et al 2015). These characteristics are not fixed however.…”
Section: Discussionsupporting
confidence: 63%
“…There was a general consensus as to what the most important operational features are and a high degree of belief in the venture. This is something that has been identified in other, mostly US, studies (Goldenhar et al 2013;Verschoor et al 2007;Freitag & Carroll 2011;Donnelly et al 2017;Glymph et al 2015;Wagner et al 2015). These characteristics are not fixed however.…”
Section: Discussionsupporting
confidence: 63%
“…Previous success stories of team building and coordination provided encouragement as we planned improvements in our unit. One paediatric radiology department implemented the daily safety huddle, 7 and another study in the UK showed the positive impact of huddles in a sample of National Health Service (NHS) paediatric wards where the Situation Awareness For Everyone (SAFE) programme was implemented. The huddle was a central component of the programme.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, the huddle has been increasingly practiced and reported in the medical setting. 7,[10][11][12] Its features generally include a short duration, the reporting of safety and quality events, enumeration of critical metrics of operation, and close communication among attendees for immediate feedback. Our laboratory medicine division huddle, structured on common elements in a laboratory huddle 7 was helpful in encouraging interteam interactions and monitoring key quality metrics.…”
Section: Discussionmentioning
confidence: 99%